Impact of socio-economic profiles on public health crisis of road traffic accidents: A qualitative study from South India - Devajana Chinnappa Nanjunda (Elsevier, 2021)
Background: Despite flows in transport policy, it is noticed many more proven wider social factors distressing the number of road traffic accidents including injuries and deaths. A wider social determinants among low socioeconomic groups including identity crises largely contributes towards an increased rate of road accidents today in india. Aim: The major aim of this paper is to provide evidence of why more road accident occurrence is distributed through Indian marginalized society, and explicitly between diverse and low socioeconomic groups and reasons thereof. Method: This first-ever study has been done in South Karnataka-India among 33 accident survivors exclusively from the marginal groups using a purposive sampling technique, participated in qualitative interviews, and focus group studies. Data has been analyzed using suitable statistical software's. Result: The result showed a valid and reliable direction regarding the association of different low socio-economic issues as a key factor for road accidents specifically among disadvantaged youths. Distinct social disparities, deprivation, social exclusion lead to identity crises which play a key role in causing more risk for road accidents among the underprivileged sections. The rate of injuries or death is also determined by the exposure to risk, which can differ between different socioeconomic groups. Conclusion: It is noted that higher levels of deprivation lead to a higher fatal injury rate or death among low socioeconomic groups. Identity crisis because of low socio-economic profile turning a deprived, marginalized, vulnerable, and excluded people especially adults shows risky and adventurous driving. There is a need to have preventive and behavioral modification for high-risk groups.